Effect of low level laser and low intensity pulsed ultrasound therapy on bone remodeling during orthodontic tooth movement in rats - Mahmood Jawad Alazzawi, Mohammed; Husein, Adam; Alam, Mohammad Khursheed; Hassan, Rozita; Shaari, Rumaizi; Azlina, Ahmad; M. S., Salzihan (Springer, 2018)
Background: Quality bone regeneration, which leads to the improvement of bone remodeling, is essential for orthodontic treatment. In order to improve bone regeneration and increase the amount of tooth movement, different techniques have been implemented. The object of this study is to compare the effects of low-level laser therapy (LLLT), low-intensity pulsed ultrasound (LIPUS), and their combination on bone remodeling during orthodontic tooth movement. Methods: Eighty (80) male, 6-week-old Sprague Dawley rats were grouped in to four groups, the first group was irradiated with (940 nm) diode laser, second group with LIPUS, and third group with combination of both LLLT and LIPUS. A forth group used was a control group in an incomplete block split-mouth design. The LLLT and LIPUS were used to treat the area around the moving tooth once a day on days 0–7, then the experiment was ended in each experimental endpoint (1, 3, 7, 14, and 21 days). For amount of tooth movement, models were imaged and analyzed. Histological examination was performed after staining with (hematoxylin and eosin) and (alizarin red and Alcian Blue) stain. One step reverse transcription-polymerase chain reaction RT-PCR was also performed to elucidate the gene expression of RANK, RANKL, OPG, and RUNX-2. Results: The amount of tooth movement, the histological bone remodeling, and the RT-PCR were significantly greater in the treatment groups than that in the control group. Among the treatment groups, the combination group was the highest and the LIPUS group was the lowest. Conclusion: These findings suggest that LLLT and LIPUS can enhance the velocity of tooth movement and improve the quality of bone remodeling during orthodontic tooth movement.